MONETARY POLICY AND INFLATION TARGETING IN A SMALL OPEN ECONOMY - Antoni Antoni (Economic Journal of Emerging Markets, 2011)
The danger of inflation has been the focus of many central banks. This paper analyzes the transmission mechanism of monetary policy and inflation targeting in Malaysia with a backward-looking aggregate supply and demand analysis. The manage floating regime applied in the country has an important role in achieving a stable exchange rate against its major trading partners. It also analyzes the policy of maintaining the soundness of interest rate to perceive inflation targeting to increase its economic growth. Using 1991-2004 data and a traditional structural econometric model, it shows that output gap is important in forecasting a domestic inflation rate by controlling the interest rate.